A real-time ultrasound process tomography system using a reflection-mode reconstruction technique. (March 2017) - Langener, Sascha; Vogt, Michael; Ermert, Helmut; Musch, Thomas
Abstract: The measurement of volume fractions of different components in multiphase flows is of great interest in many industrial applications. Ultrasound process tomography is especially well-suited for the differentiation of gaseous and liquid phases. This paper presents a measurement system, which was developed for real-time ultrasound process tomography, utilizing a ring of 32 ultrasound transducers on a measurement pipe. Simulations and measurements were conducted, and a reflection-mode reconstruction technique was used to obtain the system's point spread function and examine the performance on inhomogeneous configurations of water containing multiple gaseous objects. Furthermore, the possibility of increasing the measurement rate by reducing the number of excitations and its effects on the quality of the reconstructed images is investigated. Abstract : Highlights: Non-invasive real-time ultrasound process tomography system is presented. Reflection-mode reconstruction technique employed on simulation and measurement results. Performance is evaluated by means of the point spread function. Increase of the measurement rate by reduction of the numbers of transmitters is investigated.